Natural processes and dynamics of the coastal zone of Paros Island (Cyclades Islands of Aegean Sea) towards its sustainable development. - Evelpidou, N.; Poulos, S.; Vassilopoulos, A. (6th International Symposium Computer Mapping and GIS for Coastal Zone Management, 2003)
This study is dealing with the natural environment of the coastal zone of Paros island chosen as a representative ‘sample’ of the Cyclades complex of islands and amongst the most touristic ones. More than 75% of the coastal zone consists of high and lower cliffs, whilst relatively flat (slopes <2,5%) coastal plains do not exceed the 17% of the coastline. The island receives a considerable amount of wave energy; this has its highest values (>1500 W/m) at the NE part of the island and its lowest at the SE “protected” and shallower shelf area. Touristic (sandy/pebble) beaches have been developed along those parts of the coastline characterized by Quaternary (erodible) lithology associated with moderate wave activity. Sea level rise during the Holocene has played also an important role in coastal geomorphology; for example, Paros was connected to Naxos and Antiparos islands 10.000 yr BP and to Antiparos 6000 yr BP. A further rise of sea level (some 0,5 m at the year 2100) due to climatic changes will obviously deteriorate the terrestrial part of the coastal environment and especially all the touristic beaches and related establishments along its coastline.